Artificial intelligence of things: society readiness - Yuniarto, Dwi; Subiyakto, A'ang (Institute of Advanced Engineering and Science, 2025)
The convergence of artificial intelligence (AI) and the internet of things (IoT), known as the artificial intelligence of things (AIoT), represents a transformative leap in technology. This study investigated societal readiness for AIoT adoption and identified key factors influencing the readiness. The researchers used technology readiness index (TRI) model and broken down the model into the online survey’s instrument. The study used about 129 samples for examining the used variables, i.e., perceptions of innovation, technological skills, social and cultural influences, regulatory factors, and digital literacy. The authors employed partial least squares structural equation modeling (PLS-SEM) method using SmartPLS 3.0 to analyze the relationships between the variables of the model. The results highlighted innovation as a significant driver of societal readiness, while factors like discomfort have a lesser impact. Security and optimism also played moderate roles in shaping readiness. These findings offer crucial insights for stakeholders of the AIoT implementation by providing a foundation for strategies that promote the successful integration of AIoT into society. The study contributes to the broader discourse on technology adoption, offering a roadmap for enhancing societal preparedness.